ANOMALY OF LOW SPREAD OF COVID-19 IN SLUM SETTLEMENTS OF DEPOK VILLAGE - Imam Budi Hartono; Lin Yola; Chotib Chotib (Sosiohumaniora, 2022)
Two residents of Depok City, West Java, were confirmed as the first Covid-19 patients in Indonesia on March 2, 2020. This global pandemic has wreaked havoc on many facets of human life, especially slum environment in Depok City. Slum settlements are associated with dense populations, small streets, and disorganized housing structures, and all of which contribute to the high spread of Covid-19. In Depok Village, which is classified as a slum settlement, the number of Covid-19 case is lower than in Mekarsari Village, which is neither slum nor tend to be luxury. This study uses qualitative methods and research sources are from field observations and comparisons with previous studies which are contradictory. The theory used as a guide for this writing is Ekistics, Doxiadis. According to the findings of this study, the low number of COVID-19 cases in slum settlements can be reduced, one of the factors is the impact of improved environmental infrastructure. The Covid-19 Alert Village performance, the social community and public health also play critical roles in assisting people in their efforts to avoid the spread of Covid-19. The active participation of all members of society is the most important factor in preventing Covid-19 spread and transmission. The findings of this case study are not intended to generalize the phenomena that occur in the community, but this is an effort to evaluate and introspect on programs and policies that will be, are being, and have been performed by the local government in collaboration with the community.